Readings : the poetics of Blanchot, Joyce, Kafka, Kleist, Lispector, and Tsvetayeva - Cixous, Hélène, 1937- (Theory and history of literature, 1991)
A leader in the feminist intellectual movement, Cixous presents this highly informative meditation on ethics and poetics which draws on philosophy and psychoanalysis.